2010
DOI: 10.1164/rccm.201002-0185oc
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Epithelial Cell Injury Due to Zinc Oxide Nanoparticle Exposure

Abstract: Rationale: Although inhalation of zinc oxide (ZnO) nanoparticles (NPs) is known to cause systemic disease (i.e., metal fume fever), little is known about mechanisms underlying injury to alveolar epithelium. Objectives: Investigate ZnO NP-induced injury to alveolar epithelium by exposing primary cultured rat alveolar epithelial cell monolayers (RAECMs) to ZnO NPs. Methods: RAECMs were exposed apically to ZnO NPs or, in some experiments, to culture fluid containing ZnCl 2 or free Zn released from ZnO NPs. Transe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 49 publications
(84 reference statements)
3
53
1
Order By: Relevance
“…It is well known that ROS can interact with biomolecules including DNA and causes DNA single or double strand breaks and it is also well known that MDA causes free radicals. Some studies have reported similar results (Jeng and Swanson 2006;Musarrat et al 2009;Lin et al 2009;Gerloff et al 2009;Zhu et al 2009;Kim et al 2010). Our findings also clearly demonstrate that ZnO is clastogenic in human lymphocytes in vitro.…”
Section: Discussionsupporting
confidence: 89%
“…It is well known that ROS can interact with biomolecules including DNA and causes DNA single or double strand breaks and it is also well known that MDA causes free radicals. Some studies have reported similar results (Jeng and Swanson 2006;Musarrat et al 2009;Lin et al 2009;Gerloff et al 2009;Zhu et al 2009;Kim et al 2010). Our findings also clearly demonstrate that ZnO is clastogenic in human lymphocytes in vitro.…”
Section: Discussionsupporting
confidence: 89%
“…38 Mitochondrial activity was decreased, while LDH release and intracellular ROS were increased. Tight junctions were disrupted.…”
Section: +mentioning
confidence: 97%
“…Also, Kim et al (2010) exposed primary cultured rat alveolar epithelial cell monolayers to ZnO NPs and observed injury of the cells in dose-and time-dependent manner caused at least partially by free Zn ions released from ZnO NPs, mitochondrial dysfunction and increased intracellular ROS.…”
Section: Oxidative Stress and The Related Effects Of Nanoparticlesmentioning
confidence: 99%